Catolicismo Ultramontano e relações sociais nas cartas pastorais e nas correspondências recebidas por D. Fernando de Sousa Monteiro, Bispo da Diocese do Espírito Santo (1901-1916) - Costa, Cintia Moreira da (2023)
The research aimed to understand the role played by Dom Fernando de Sousa Monteiro, CM, Bishop of the Diocese of Espírito Santo/Brazil, between the years 1901 and 1916, in the sociopolitical and religious scenario of Espírito Santo during the First Republic. Coming from a rich family of farmers in the southern region of that state, Dom Fernando Monteiro played an important role in the consolidation of the Diocese of Espírito Santo, by implementing in his jurisdiction the practice of Catholicism in line with the ultramontane principles emanating from the Holy See. Bishop was also recognized for his skills in conciliation and political advice, having even been responsible for nominating candidates for the position of president of the state, according to the episode of his brother Jeronymo Monteiro's candidacy for state succession in 1908, at a time serious regional political crisis. To better understand this action, in an ultramontane context, several encyclicals by Leo XIII and Pius X were analyzed, as well as the pastoral letters published by Dom Fernando Monteiro during the period in which he was at the head of that Diocese. In addition, letters exchanged with family and close friends were analyzed in order to understand the network of information and favors that surrounded the Bishop. Among the objectives are the understanding of the process of implementing ultramontane Catholic practices in Espírito Santo, the repositioning of the Catholic Church in the face of the new Brazilian republican legal system – which determined the secularity of the State – as well as the relationships established between that prelate and members of society local.